THE FLAVOR OF NAMES: HOW YOGYAKARTA CAFÉS BRAND THEIR BEVERAGES - Fitria Amanda; Ajar Pradika Ananta Tur (Lire Journal (Journal of Linguistics and Literature), 2026)
This research investigates the impact of beverage names on consumers' perceptions and decisions. For instance, names like "fruity loop" evoke specific feelings that may affect buying choices. Brand theory emphasizes the significance of menu names in defining a café's character, as such names play a crucial role in drawing in customers and enhancing their satisfaction. Culinary linguistics asserts that the names of products play a crucial role in the branding and communication of food and beverages. The names of drinks in cafés in Yogyakarta showcase naming trends that represent identity, values, and the customer experience, while also linking culinary language and marketing strategies.This study uses qualitative descriptive analysis to collect linguistic and cultural data through field observations. The study consists of four steps: collecting drink menus from well-known and diverse cafes in Yogyakarta, classifying drink names, taking photos and notes of the menus, and conducting in-depth data analysis. Key information includes beverage menu names called “culinaronyms,” which describe language, meaning, and culture. These names are important for products because unique names have the potential to attract consumers. This study highlights the linguistic features found in unique beverage menu titles, such as Vietnam Drip, Black Citrus, and Caramel Macchiato. These names were collected from cafes in Yogyakarta using Google Maps, Instagram, and YouTube. They combine narrative and imaginative language to build brand identity and express social and cultural values. The naming approach uses foreign vocabulary, figurative language, and unique linguistic creativity. This study analyzes the naming patterns of cafes in Yogyakarta, showing that beverage names reflect the personality and image of the cafe. These names are also classified based on meanings related to product identity, cultural connections, and emotional reactions.